ANALISIS TINGKAT DENGUNG PADA RUANG SERBAGUNA (Studi Kasus Gedung Guru Jakarta) - Syahida Wafa; Novita Vita; Atie Ernawati; Ryan Hidayat; Muhammad Sega Sufia Purnama (Lakar: Jurnal Arsitektur, 2020)
The purpose of this study was to determine the level of reverberation in the multipurpose room, a case study of the Jakarta teacher building. The research method used is a quantitative method, with the calculation of reverberation time (Buzz Time) with the Sabine formula method. Based on the reverberation time calculation that has been carried out by the researcher, the level of reverberation in the multipurpose hall of the Jakarta teacher building is 3.3 seconds, which does not meet the standard as a multipurpose auditorium space, namely 1.5 to 1.7 seconds.